The Performance of the Asset Management Companies in the US - Rompotis, Gerasimos (International Journal of Finance Research, 2024)
This paper seeks to identify the factors that may affect the financial performance and stock return of Asset Management Companies (AMCs) in the United States. The study focuses on a sample of fifty listed AMCs and uses data for the four years 2019-2022. Financial performance is computed as Return on Assets, Return on Equity, and Return on Capital Employed. Stock return is calculated with monthly and annual stock price data. Liquidity, solvency, and efficiency factors are used as explanatory variables, along with the size of the companies. The results show that the financial performance is negatively related to the debts-to-assets ratio. The opposite relation is found for stock return. The impact of the debt-to-equity ratio on performance is positive. This is also the case for assets turnover, net cash flow-to-assets ratio, and size.